2013
DOI: 10.1039/c3dt50416f
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-ligand copper(ii)–sulfonamide complexes: effect of the sulfonamide derivative on DNA binding, DNA cleavage, genotoxicity and anticancer activity

Abstract: Four ternary complexes, [Cu(L1)2(bipy)] (1) [HL1 = N-(6-chlorobenzo[d]thiazol-2-yl)-4-methylbenzenesulfonamide], [Cu(L2)2(bipy)] (2) [HL2 = N-(benzo[d]thiazol-2-yl)-4-methylbenzenesulfonamide], [Cu(L3)2(bipy)]·1/2H2O (3) [HL3 = N-(5,6-dimethylbenzo[d]thiazol-2-yl)-4-methylbenzenesulfonamide] and [Cu(L4)2(bipy)] (4) [HL4 = N-(5,6-dimethylbenzo[d]thiazol-2-yl)benzenesulfonamide], were prepared and then characterized by X-ray crystallography, spectroscopy and magnetic measurements. Whereas the molecular structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 72 publications
1
19
0
Order By: Relevance
“…Among the different classes of sulfonamide drugs, those with nuclease and/or cytotoxic activity are receiving increasing attention in the search for anticancer chemotherapeutic strategies. [9][10][11][12][13] Over recent years, the conformational preferences of sulfonamides have been actively exploited in drug design, as the conformation defines the shape of the molecule, which in turn is a major determinant of its biological and physical properties. [14,15] Many structural studies have been performed on N-tosylsubstituted Schiff bases, because the rigidity of the sulfonamide functional group typically favours crystallisation.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different classes of sulfonamide drugs, those with nuclease and/or cytotoxic activity are receiving increasing attention in the search for anticancer chemotherapeutic strategies. [9][10][11][12][13] Over recent years, the conformational preferences of sulfonamides have been actively exploited in drug design, as the conformation defines the shape of the molecule, which in turn is a major determinant of its biological and physical properties. [14,15] Many structural studies have been performed on N-tosylsubstituted Schiff bases, because the rigidity of the sulfonamide functional group typically favours crystallisation.…”
Section: Introductionmentioning
confidence: 99%
“…This may suggest that conjugation of biologically active peptides with quinoxaline analogs can lead to new therapeutic agents possessing interesting anticancer properties (Ambika et al, 2013;Staszewska, Stefanowicz, & Szewczuk, 2005). In addition, quinoxaline derivatives are reported for their applications in dyes, efficient electroluminescent materials, organic semiconductors, and DNA cleaving agents (González-Álvarez et al, 2013;Srinivas, Kumar, Rao, & Palaniappan, 2008). Surfactants, sometimes called surface-active agents or detergents, are among the most versatile chemicals available.…”
Section: Please Scroll Down For Articlementioning
confidence: 98%
“…González-Álvarez et al, for example, reported copper(II)-bpy complexes with thiazol-sulfonamide derivatives with nuclease activities that correlated with their cytotoxicity on the low micromolar range against human Jurkat T lymphocytes and Caco-2 cell lines. The complexes induced cell death by an apoptotic mechanism [10]. The same research group reported copper complexes of N-substituted sulfonamides that presented DNA photocleavage and remarkable cytotoxicity on sub-micromolar range against Caco-2 cell lines [25].…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of [Cu(phen) 2 ] 2+ , much effort has been dedicated to the development of novel artificial metallonucleases, since metal complexes are endowed with several properties that can be explored to fine-tune the desired nuclease activity. This includes the number and nature of the ligands, structural diversity and electronic properties [5,7,10]. For reviews of artificial copper metallonucleases, the reader is directed to the works of McGivern et al [7] and Pratviel et al [11].…”
Section: Introductionmentioning
confidence: 99%